The National Conference of Black Political Scientists (NCOBPS): Organizational Empowerment Through Signaling and Valuing Women and Diversity During #MeToo. (2nd January 2019) - Nunnally, Shayla C.
ABSTRACT: The National Conference of Black Political Scientists (NCOBPS) is an almost 50-year-old organization. Its history is rooted in challenging racial discrimination and exclusion of people of African descent in the political science discipline and profession. Over time, the organization also has sought diversity and inclusion in various forms, whether through inclusion of intersectional identities and expressions or philosophical perspectives. This article describes the significance of signaling inclusive values through the institutionalization of the organization. It also offers best practices for the #MeToo movement through accounting for inclusive practices of NCOBPS.